A Review of Cross-Referencing from Arabic Poetry in Tafsār Zād al Masīr by Ibn al Jawzī - Alazhari, Muhammad Riaz; Israr, Muhammad (Journal of Islamic and Religious Studies, 2016)
This paper describes that if we want to know about poetry we must understand that out of context we can never arrive at our destination. The Qur‘ān should be read and understood in totality of its message and spirit. Its verses are local and universal. Some verses are in local environments but leave universal and external message. The verses of Sūrah Yāsīn and Sūrah Najm related to poetry clearly exhibit the truth that God rejected the claim of the infidels who regarded the Qur‘ān as the book of poetry and Prophet Muhammad as a poet. It is an apt reply to the infidels that Qur‘ān is a message of God with a serious mission and motto. The Holy prophet used to ask people to recite the Holy poetry of Abu ║ālib. ╓assān bin thābit used to recite ‘Nāt’ in the presence of the Prophet. They enhanced the divine mission of the prophets through their facile pen and noble spirit. Hence in the light of above brief dissertation we can profess that Islam does not oppose poetry if it is written on didactic and divine lines.